Absorption and Excretion of Diquat and Paraquat in Rats - Daniel, J. W. (1966)
The fate of (14)C-labelled diquat and paraquat after oral and subcutaneous administration of single doses has been studied in the rat. By both routes of administration the radioactivity usually appears in the excreta within two days. In a few cases a small amount is excreted in the urine on the third day or in faeces on the fourth day. After an oral dose of paraquat no radioactivity could be detected in bile, and with diquat less than 5% of the dose appeared in bile within 24 hours. Both diquat and paraquat are poorly absorbed from the gut, and after subcutaneous administration little or none appears in faeces. By comparison of the measurements of radioactivity with a specific chemical test for diquat and paraquat, the presence of a small amount of metabolites in the urine after oral dosing has been detected. As no such metabolism has been observed after subcutaneous administration it seems probable that there is some absorption of degradation products formed within the gut. It has been shown that about 70% of an oral dose of diquat and about 30% of a dose of paraquat is present in faeces as metabolic products. In vitro experiments have shown that this is probably due to microbiological degradation in the gut.